The role of midwives in supporting the development of the mother-infant relationship: a scoping review - Cathy Stoodley; Lois McKellar; Tahereh Ziaian; Mary Steen; Jennifer Fereday; Ian Gwilt (BMC Psychology, 2023)
Abstract Background The mother-infant relationship is complex and dynamic, informing the psychological development of the infant through bonding and attachment. Positive early interactions influence the quality of this relationship. Midwives are well placed to support the developing relationship between the mother and baby, yet there has been limited research exploring the role of the midwife in this context. Aim To explore interventions that have been provided by the midwife which support the development of the maternal-fetal or mother-infant relationship amongst a low-risk population from pregnancy, and up to six weeks postnatal. The review also sought to understand the types of interventions developed, format and delivery, outcomes measured and if cultural considerations had been incorporated. Methods A scoping review of the research literature was undertaken using the Joanna Briggs Institute framework. Five online databases were searched for relevant articles published in English from 2000 to 2021. Findings Sixteen articles met the inclusion criteria. Three themes emerged: (1) viewing the fetus as separate from the mother, (2) focused activities on the maternal-infant relationship and (3) targeted educational interventions. Discussion Providing focused activities and targeted education during the pre and postnatal periods support the development of the mother-infant relationship. Significantly, there was insufficient research that considered the influence of culture in supporting the mother-infant relationship. Conclusion Further research is required to develop interventions that include a diverse sample to ensure culturally appropriate activities can be integrated into care during pregnancy and/or the postnatal period provided by midwives.